The influence of elevated levels of C‐reactive protein and hypoalbuminemia on survival in patients with advanced inoperable esophageal cancer undergoing palliative treatment. Issue 6 (29th June 2014) - Lindenmann, Joerg; Fink‐Neuboeck, Nicole; Koesslbacher, Mario; Pichler, Martin; Stojakovic, Tatjana; Roller, Regina Elisabeth; Maier, Alfred; Anegg, Udo; Smolle, Josef; Smolle‐Juettner, Freyja Maria
<x xml:space="preserve">Abstract</x> Background and Objectives Inflammation perpetuates individual tumor progression resulting in decreased survival in cancer patients. The aim of our study was to evaluate the influence of elevated levels of C‐reactive protein (CRP) as well as low levels of albumin on patients with inoperable esophageal carcinoma. Methods The data of 218 patients with advanced esophageal cancer, who were treated at a single center within 12 years, were evaluated retrospectively. Patient's age, gender, body weight, dysphagia, plasma levels of CRP and albumin, the Glasgow Prognostic Score (GPS) combining both indicators, and survival were assessed for statistical evaluation. Results Thirty‐nine (18.2%) had hypoalbuminemia and 161 (73.9%) had elevated CRP levels. Patients with hypoalbuminemia (P = 0.001) as well as patients with increased CRP levels (P = 0.001) showed a significantly shorter survival. Weight loss was correlated to elevated plasma CRP (P = 0.022), to diarrhea (P = 0.021), and to dysphagia (P = 0.008). Increasing GPS was significantly associated with poor survival (P = 0.001). Conclusions Elevated CRP levels and hypoalbuminemia are significantly associated with reduced survival and are considered to be an appropriate predictor for poor outcome in advanced esophageal carcinoma. The GPS provides additional detailed prognostication and should be therefore taken into consideration when the individual palliative strategy has to be scheduled. J. Surg. Oncol. 2014 110:645–650. © 2014 Wiley Periodicals, Inc.